Revitalizing Islamic Cultural History: The Impact and Implementation of Online Learning - Muntohar Muntohar; Nabiswa Martin Wasike (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to provide an overview of the process and results of implementing online learning in Islamic cultural history subjects at State Islamic High School 2 Cilacap. Methodology: The type of research used by researchers in this research is field techniques using a qualitative descriptive approach. Main Findings: The results of this research include the objectives of online learning for the history of Islamic culture at State Islamic High School 2 Cilacap, which consists of e-learning based learning to make learning materials accessible to other people. The benefits of online learning are to overcome space and time limitations between teachers and students. The advantages and obstacles of online learning. Novelty/Originality of this study This research provides a unique contribution by presenting specific information about the implementation of online learning in the Madrasah Aliyah environment with a focus on the history of Islamic culture. This can be a reference and source of inspiration for further research in a similar context.